Production and characterization of shape memory epoxy foam by an advances aqueous method / \c Muhammad Syazwan Bin Fauzi. - Muhammad Syazwan Fauzi (School of Materials Engineering, Universiti Malaysia Perlis, 2015)
The research objectives are to investigate the effect of epoxy-polyamide ratio on the foam morphology, mechanical strength, memory shape properties and thermal properties of shape memory epoxy foam; to study the effect of blowing agent (sodium bicarbonate) content on foaming behaviour as well as on foam morphology, mechanical strength, memory shape properties and thermal properties; and to study the effect of eggshell filler's content on the foam morphology, mechanical strength, memory shape properties and thermal properties of shape memory epoxy foam.